Detection fimH Gene in The Urine of UTI Patients at The Puskesmas Banyuanyar, as a Marker for The Presence of Escherichia coli - Sawitri, Debora; Dewangga, Vector Stephen; Qurrohman, Muhammad Taufiq (Jurnal Biologi Tropis, 2024)
Urinary Tract Infection (UTI) is a bacterial infection characterized by a urine culture showing bacteriuria with bacterial counts exceeding 100,000 per milliliter of urine. Polymerase Chain Reaction (PCR) is a method that utilizes in-vitro enzymatic reactions to amplify specific DNA targets. This process synthesizes new DNA strands complementary to the target sequences using enzymes and oligonucleotide primers within a thermocycler. The fimH gene is among the most important of the UPEC strains and is associated with severe urinary tract infections. The aim of this study was to identify the presence of the fimH gene in urine samples from UTI patients at the Puskesmas Banyuanyar in Surakarta using Polymerase Chain Reaction (PCR). The research employed the Quota Sampling Technique, collecting a total of five urine samples from individuals diagnosed with urinary tract infections. The results of the control isolates using pure Escherichia coli isolates showed that the fimH gene PCR amplified control with annealing temperature of 52°C. The analysis of clinical isolates of Escherichia coli from the urine of urinary tract infection patients revealed that the fimH gene was PCR amplified in all five samples.